The art of governing youth: Empowerment, protagonism, and citizen participation - Raposo, O. (Social Inclusion, 2022)
This article discusses social inclusion policies for youth from vulnerable socioeconomic contexts, based on the ethnographic monitoring of an associative experience promoted by the “Choices Programme” (“Programa Escolhas”) on the outskirts of Lisbon. Considered the main public policy directed at poor, racialised and peripheral youth in Portugal, the Choices Programme is driven by strategies of empowerment and protagonism with a view to engaging youngsters in resolving the problems faced in the neighbourhoods in which they live. Both strategies call for citizen participation, but restrict the youth’s field of political action to the rules drawn up by the State, discouraging emancipatory and subversive discourse. The result is biopolitical control and management of marginalised youth masking a domination that has domesticated their collective action. By recreating the meetings and activities that sought to inspire in these youngsters the virtues of associativism, I discuss how the discourses of empowerment and protagonism are incorporated as new devices of agency and community governmentality. In particular, I question the limits of citizen participation as a means to stimulate the political engagement of youth when this is tied to individualist ideologies distant from a grammar of rights.